THE EFFECT SODIUM HYPOCHLORITE 2,5% AND SODIUM THIOSULPHATE AS IRRIGATION ON THE CLEANLINESS OF THE APICAL THIRD ROOT - Christina Mahardika; Yulita Kristanti; Margareta Rinastiti (ODONTO : Dental Journal, 2022)
Background: Sodium hypochlorite produces free oxygen and free radicals that cause damage to dentin collagen. Combination with Sodium thiosulfate with the aim of improving root canal hygiene and restoring the oxidizing effect on the dentin surface.The apical third of the root canal is the most difficult part, due to its narrower anatomy, curvature and frequent branching of the root canal. Method: The study used 30 specimens which were divided into 3 groups, group I was irrigated with 2.5% NaOCl, 5% sodium thiosulfate and saline, group II was irrigated with 2.5% NaOCl, 10% sodium thiosulfate and saline and group III was irrigated with 2.5% NaOCl and saline. The tooth length 14 mm measured from apical to crown. The crown down technique was prepared using the M3 Pro gold file. Observation of the level of cleanliness of the root canal was carried out using a Scanning Electron Microscope (SEM) with 5000x magnification at apical third . The results of micrographic photographs are then given a score of 1-4.Result: Irrigated with 5% and 10% sodium thiosulfate showed no significant difference.Conclusion: The differences is not significant, 2,5% irrigation with sodium thiosulfate resulted in a higher cleanliness apical third of the root canalthan 2,5% NaOCl irigation with saline